DESAIN DAN UJI COBA GAME EDUKASI KIMIA BERBASIS ROLE PLAYING GAME (RPG) PADA MATERI LAJU REAKSI - Ahmad Harianto; Elvi Yenti (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2021)
This research aimed at developing chemistry education game of role playing game (RPG) based on the reaction rate material and to know product quality based on assessment of media, material experts and chemistry teacher subject. This research used the research and development method which refers to development models from Borg and Gall. The conclusion of this research was the chemistry education game of role playing game (RPG) on reaction rate based that was developed fulfills the criteria both of as a media learning chemistry independence. The media expert gave good scores (75.00%), the material expert gave good scores (80.00%), the teachers gave very good scores (92.00%). In the first filed try out, the students gave very good responses (92.10%). The qualitative assessment was suggestions from validators, teachers and students who said that chemistry education game of role playing game (RPG) based on the material of the factors influencing reaction rate have been said good.